1987
DOI: 10.1177/036354658701500415
|View full text |Cite
|
Sign up to set email alerts
|

Injury to the brachial plexus during Putti-Platt and Bristow procedures

Abstract: Eight patients with documented recurrent anterior dislocation of the shoulder sustained iatrogenic brachial plexus injuries during either Putti-Platt or Bristow procedures. Two patients also sustained axillary artery injuries. There were six males and two females. Postoperatively, complete paralysis of the musculocutaneous nerve was noted in six cases and incomplete paralysis in one case. Two patients had complete axillary nerve palsies. There were two cases of partial paralysis of the radial, median, and ulna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0
2

Year Published

2001
2001
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(26 citation statements)
references
References 13 publications
0
24
0
2
Order By: Relevance
“…Study details including patient demographics, follow-up characteristics and details of previous surgery are presented in Table I. These 30 studies described the results of 1658 open coracoid transfer procedures for shoulder instability. Three percent of cases (20 of 636) from 14 studies 1,5,6,9,13,[15][16][17]19,22,24,32,41,45 were revision procedures. Sixteen studies 4,12,29,31,33,36,39,[43][44][45]47,[49][50][51][52][53] (1058 cases) made no comment regarding whether the procedures were primary or revision cases.…”
Section: Resultsmentioning
confidence: 99%
“…Study details including patient demographics, follow-up characteristics and details of previous surgery are presented in Table I. These 30 studies described the results of 1658 open coracoid transfer procedures for shoulder instability. Three percent of cases (20 of 636) from 14 studies 1,5,6,9,13,[15][16][17]19,22,24,32,41,45 were revision procedures. Sixteen studies 4,12,29,31,33,36,39,[43][44][45]47,[49][50][51][52][53] (1058 cases) made no comment regarding whether the procedures were primary or revision cases.…”
Section: Resultsmentioning
confidence: 99%
“…Sungpet et al (1998) have suggested that the position of the shoulder dur-ing dissection can affect recorded measurements, since the MCN is anchored to the CB. Many authors have suggested that the point of entry of the MCN into the CB is clinically important (Latarjet, 1954;Helfet, 1958;Richards et al, 1987;Flatow et al, 1989;Resch et al, 1996), and a correlation between more highly positioned points of penetration and frequency of nerve injuries has been reported.…”
Section: Discussionmentioning
confidence: 99%
“…2,12,17 In addition, injury due to incorporation of a nerve into the repair construct for open shoulder instability procedures has been reported for the axillary, median, musculocutaneous, and ulnar nerves. 22 Suprascapular nerve injury after the Latarjet procedure has also been described. 19 In this instance, a screw tip interred the spinoglenoid notch, with full recovery of function after removal of the screw.…”
Section: Discussionmentioning
confidence: 99%
“…19 Other proposed mechanisms of nerve injury after BristowLatarjet procedures have included laceration and traction injuries. 22,24 Although injury to the musculocutaneous nerve during the Bristow-Latarjet procedure is well documented, delayed dysfunction is atypical. Bach et al 3 described a patient who experienced delayed paresthesias after a modified Bristow procedure.…”
Section: Discussionmentioning
confidence: 99%